C/EBP maintains chromatin accessibility in liver and facilitates glucocorticoid receptor recruitment to steroid response elements. (10th May 2013) - Grøntved, Lars; John, Sam; Baek, Songjoon; Liu, Ying; Buckley, John R; Vinson, Charles; Aguilera, Greti; Hager, Gordon L
<x xml:space="preserve">Abstract</x> Mechanisms regulating transcription factor interaction with chromatin in intact mammalian tissues are poorly understood. Exploiting an adrenalectomized mouse model with depleted endogenous glucocorticoids, we monitor changes of the chromatin landscape in intact liver tissue following glucocorticoid injection. Upon activation of the glucocorticoid receptor (GR), proximal regions of activated and repressed genes are remodelled, and these remodelling events correlate with RNA polymerase II occupancy of regulated genes. GR is exclusively associated with accessible chromatin and 62% percent of GR‐binding sites are occupied by C/EBPβ. At the majority of these sites, chromatin is preaccessible suggesting a priming function of C/EBPβ for GR recruitment. Disruption of C/EBPβ binding to chromatin results in attenuation of pre‐programmed chromatin accessibility, GR recruitment and GR‐induced chromatin remodelling specifically at sites co‐occupied by GR and C/EBPβ. Collectively, we demonstrate a highly cooperative mechanism by which C/EBPβ regulates selective GR binding to the genome in liver tissue. We suggest that selective targeting of GR in other tissues is likely mediated by the combined action of cell‐specific priming proteins and chromatin remodellers.